2008
DOI: 10.1111/j.1369-1600.2007.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOMARKER: Assessment of alcohol consumption among hepatitis C‐positive people receiving opioid maintenance treatment using direct ethanol metabolites and self‐report: a pilot study

Abstract: This study was conducted to identify the alcohol consumption among hepatitis C-positive people receiving opioid maintenance therapy using self-report and biomarkers. A total of 49 people (28 male, 21 female) were hepatitis C virus (HCV) positive and were included. The alcohol use disorder identification test (AUDIT) and self-reported ethanol intake in the last 28 days were assessed. In addition to gamma-glutamyl-transferase (GGT) and mean corpuscular volume (MCV), ethyl glucuronide (EtG) and ethyl sulphate (Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…These compounds were already determined in other biological matrices in an attempt to diagnose acute (blood and urine) or chronic (hair) ethanol misuse in adults [11][12][13][14][15][16][17]. Our preliminary results demonstrated that both EtG and EtS could discriminate between samples which tested negative and those which tested positive for prenatal ethanol exposure, as evidenced by cumulative meconium FAEEs < and !2 nmol/g [18,19].…”
Section: Introductionmentioning
confidence: 72%
“…These compounds were already determined in other biological matrices in an attempt to diagnose acute (blood and urine) or chronic (hair) ethanol misuse in adults [11][12][13][14][15][16][17]. Our preliminary results demonstrated that both EtG and EtS could discriminate between samples which tested negative and those which tested positive for prenatal ethanol exposure, as evidenced by cumulative meconium FAEEs < and !2 nmol/g [18,19].…”
Section: Introductionmentioning
confidence: 72%
“…Increased mean corpuscular volume (MCV) or carbohydrate-deficient transferrin values are other relevant biomarkers for alcoholism [30,31,32]. More recently, direct alcohol metabolites, especially ethyl glucuronide, was reported to be useful for measuring alcohol consumption in patients on opioid maintenance therapy [33,34,35]. Also, the 5HTOL/HIAA ratio in urine was used to detect alcoholism in methadone maintenance patients [36].…”
Section: Diagnosis Of Aud In Opioid Dependencementioning
confidence: 99%
“…The comparison of the DRI-EtG EIA with a reference LC-MS method for 126 urine samples (100-50,000 ng/ml) was made with Passing-Bablok regression (EIA = -0.104 + 0.960 LC-MS). Both methods showed an overall good and statistically significant agreement r 2 = 0.961 (p < 0.0001) [25] .…”
Section: Etg Measuringmentioning
confidence: 88%
“…This fact might yield relevant consequences, such as the fact that patients from experimental settings might differ significantly from patients in routine settings [19,20] , ultimately jeopardizing the feasibility, applicability and even the relevance of experimental findings [21] . Other concerns regarding previous EtG studies are small sample sizes or the use of inpatient populations [22][23][24][25] . Therefore, we believe that it is important to assess the performance of EtG in 'the real world'.…”
mentioning
confidence: 99%